DIGITAL LIFE TEMPTATION (JEA17: Jurnal Ekonomi Akuntansi, 2022)
Technology is not something "dead". Technology is able to change anything into something that has never been thought of before by anyone. Today technology is a solution for anything and for anyone anywhere. Everything becomes more practical with the help of technology. Everyone who is interested in using it can learn it in a short time. Efforts to learn it can use in various ways that can be done by all ages. However, all new things certainly have advantages and disadvantages in them, including the latest technology. These updates have also created many new things and new opportunities for all humans on this earth. The side effects of technological developments or advances will certainly have an impact on all fields throughout the earth. One of them is financial technology, which is currently growing rapidly in Indonesia, through online loans.